2007
DOI: 10.1159/000102568
|View full text |Cite
|
Sign up to set email alerts
|

Memantine in Moderate to Severe Alzheimer’s Disease: a Meta-Analysis of Randomised Clinical Trials

Abstract: The efficacy of memantine in Alzheimer’s disease (AD) has been investigated in multiple randomised, placebo-controlled phase III trials. Recently, the indication label for memantine in Europe was extended to cover patients with moderate to severe AD, i.e. Mini-Mental State Exam total scores below 20. The efficacy data for memantine in this patient subgroup has been summarised by a meta-analysis of 1,826 patients in six trials. Efficacy was assessed using measures of global status (Clinician’s Interview-Based I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
148
1
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(181 citation statements)
references
References 43 publications
10
148
1
15
Order By: Relevance
“…A metaanalysis done in 2007 of six individual phase III studies using a subgroup of patients with moderate to severe AD showed that the drug resulted in a statistically significant benefit in four domains: namely cognitive, functional, global, and behavioural domains. The metaanalysis also highlighted a significant improvement in ADL with memantine, compared to placebo (22). A metaanalysis in 2011 found no significant differences between memantine and placebo on any outcome for patients with mild AD, either on individual trial or when data were combined (ADAS-cog 0.17; P = 0.82) (25).…”
Section: Memantinementioning
confidence: 93%
See 1 more Smart Citation
“…A metaanalysis done in 2007 of six individual phase III studies using a subgroup of patients with moderate to severe AD showed that the drug resulted in a statistically significant benefit in four domains: namely cognitive, functional, global, and behavioural domains. The metaanalysis also highlighted a significant improvement in ADL with memantine, compared to placebo (22). A metaanalysis in 2011 found no significant differences between memantine and placebo on any outcome for patients with mild AD, either on individual trial or when data were combined (ADAS-cog 0.17; P = 0.82) (25).…”
Section: Memantinementioning
confidence: 93%
“…A number-needed-to-treat (NNT) analysis of memantine Medications used in dementia: a review of evidence showed a NNT of 3-8 (19). It is indicated for the treatment of moderate to severe AD, and has shown significant efficacy in improving symptoms in several large-scale, controlled clinical studies (20)(21)(22)(23). Memantine may be effective in delaying worsening of clinical symptoms, and decreasing the emergence of BPSD (24)(25).…”
Section: Memantinementioning
confidence: 99%
“…A review of published clinical trials of memantine indicated that early treatment of hypertension, a risk factor for stroke, reduces the risk of vascular dementia and slows its progression [39]. In addition, a previous study showed that memantine may be effective in improving the memory of patients with MCI [40].…”
Section: Long-term Effects Of Combined Treatment With Memantine and Dmentioning
confidence: 99%
“…Донепезилу была свойственна более высокая частота побочных эффектов по сравнению с плацебо (особенно связанных с дисфунк-цией желудочно-кишечного тракта), и соответственно пре-парат чаще отменялся по данной причине [10,15]. Трехлетняя открытая фаза двух клинических испытаний мемантина у пациентов с умеренной и тяжелой деменци-ей при БА показала, что на фоне длительной терапии мемантином происходит практически двукратное замед-ление нарастания когнитивных нарушений [37,38].…”
Section: лекарственная терапия баunclassified